2022
DOI: 10.1161/circ.145.suppl_1.054
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 054: Hypertension Treatment And Control In A New York City Healthcare System

Abstract: Background: We investigated the prevalence of and patient characteristics correlated with hypertension control in the Montefiore Health System, a large and predominantly minority healthcare system with locations in New York City and Southern portion of Upstate New York. Methods: Using outpatient care data, we included all individuals with hypertension defined by ICD 9/10 codes during 2018. Treatment and control status were defined by the presence of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The findings showed that rates of hypertension treatment and control in the Montefiore health system were lower than the national average; Asian and White adults had a better BP control compared with Black and Hispanic adults. 54 …”
Section: Oral Abstract Presentationsmentioning
confidence: 99%
“…The findings showed that rates of hypertension treatment and control in the Montefiore health system were lower than the national average; Asian and White adults had a better BP control compared with Black and Hispanic adults. 54 …”
Section: Oral Abstract Presentationsmentioning
confidence: 99%